The Contribution of Betawi Ulama to Strengthening Islamic Education in Society - Nanda Khairiyah; Nahuda (CV ODIS, 2022)
The development of Islam in Betawi from Jayakarta to Batavia and traces the pattern of Islamic diversity in Betawi. So it can be concluded that there is an intellectual relationship between the Nusantara clerics and the Makkah and Madinah clerics as well as the reform efforts carried out by the Betawi clerics. Islam and Betawi are inseparable. Even the term